TECHNIQUE OF ESTIMATE OF ABSORPTION COEFFICIENT LASER RADIATION IN BORON DOPED DIAMONDS BY INTENSITY OF RAMAN SCATTERING - O. N. Poklonskaya (Приборы и методы измерений)
Results of measurements of Raman scattering at the room temperature in air in boron doped synthetic diamonds (five with boron concentrations 2·1017; 6·1017; 2·1018; 1,7·1019; 1·1020 cm–3 and one intentionally undoped) are presented. The laser with wavelength 532 nm was used for Raman scattering excitation. Dependences of integral intensity and halfwidth of diamond Raman line with respect to the doping level are presented. In the geometrical optics approximation an expression for doped to undoped integral intensity ratio is obtained. Qualitative estimates of conductivity of the studied samples are conducted. The obtained results can be applied for mapping of near-surface laser radiation absorption coefficient of synthetic single crystal diamonds and for their quality control.